Remittance flow determinants and the role of government policy in conflict-affected Palestinian territories - Mohammad Aref Ibrahim (Journal of Government and Economics)
This study analyzes the determinants of remittance inflow to the Palestinian territories within the framework of chronic political conflict and economic volatility. Remittances are an important source of Palestinian household finance, offering economic security in the face of labor supply shortages, trade barriers, and inflationary stress. Applying an Autoregressive Distributed Lag (ARDL) framework, the research studies the short- and long-run interrelations between remittance flows and significant macroeconomic and conflict-related variables such as conflict intensity, poverty, fluctuations in the exchange rate, trade openness, inflation, and unemployment.The empirical evidence demonstrates that remittance inflows respond sensitively to economic and political shocks. Poverty and conflict intensity have a direct and robust positive impact, consistent with the altruism hypothesis that migrants respond to crises by increasing financial flows. Migrants also respond to increasing living costs by increasing remittances. Economic hardship, however, especially if sustained, negatively affects remittance flows by constricting migration opportunities and decreasing expatriate workers' income potential. Remittance flows are positively affected by trade openness and exchange rate stability, reflecting the influence of economic integration and financial infrastructure on remittance flow behavior.The research offers solid econometric evidence for the stabilizing function of remittances for conflict economies. Whereas remittances serve as an economic buffer, their developmental contribution in the long term is hampered by consumption-driven expenditures and restrictive investment channels. Policy makers must emphasize improving financial inclusion, lowering the cost of transactions, and an investment-friendly policy to leverage remittances to the fullest extent, toward sustainable economic growth. The research also adds to the existing literature on remittances for conflict-affected economies and provides policy recommendations to maximize remittance use for maintaining economic resiliency and development for Palestine.